Triggered lightning sky waves, return stroke modeling, and ionosphere effective height. Issue 6 (24th March 2017) - Carvalho, F. L.; Uman, M. A.; Jordan, D. M.; Hill, J. D.; Cummer, S. A.; Kotovsky, D. A.; Moore, R. C.
Abstract: Ground waves and sky waves measured 209 km and 250 km south of six triggered lightning flashes containing 30 strokes that occurred in the half‐hour before sunset on 27 August 2015 are presented and analyzed. We use a cross‐correlation technique to find the ionospheric effective reflection height and compare our results to previous techniques that calculate effective height based on the time delay between ground wave and sky wave time domain features. From the first flash to the last flash there is, on average, a 1.6 km increase in effective ionospheric height, whereas no change in effective ionospheric height can be discerned along the individual strokes of a given flash. We show to what extent the triggered lightning radiation source can be described (using channel‐base current, channel geometry, and channel luminosity versus time and height) and speculate that a well‐characterized source could allow a more accurate determination of the electromagnetic fields radiated toward the ionosphere than has been done to date. We show that both channel geometry and the change in return stroke current amplitude and waveshape with channel height (inferred from measured channel luminosity versus height and time) determine the waveshape of the ground wave (and presumably the upward propagating wave that results in the sky wave) and that the waveshape of the ground wave does not appear to be related to the current versus time waveform measured at the channel base other than a roughly linear relationship between the two peak values. Key Points: First study of sky waves from triggered lightning Effective ionospheric height increases with time for six sequential flashes during one‐half hour before sunset Effective ionospheric height stays roughly constant for strokes within individual flashes